Palace of Fine Arts, San Francisco, California (Scenic View Card Co.)
Number 72 next to title of postcard. Note On verso: The Palace of Fine Arts is an example of the world's most graceful architecture. It is the only building that remains of the 1915 Panama Pacific International Exposition. It is located near the Presidio and the Marina Section.